Optimalisasi Proses Rekrutmen, Administrasi Karyawan, dan Employer Branding di PT Swalayan Sukses Abadi - Erica Purnama; Denta Felli Ananda; RR. Niken Purbasari; Setia Tjahyanti (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This report describes the author's activities in the internship process for program Magang Bersertifikat Kampus Merdeka (MBKM) program at PT Swalayan Sukses Abadi (TheFoodhall) which is part of PT Mitra Adiperkasa Tbk (MAP). This report also contains the author's daily life as an intern with PT Swalayan Sukses Abadi in the Human Capital & General Affairs division as HR Administration. What will be explained includes the division of tasks within the HC&GA division, all work assigned by the mentor to the author, both routine and non-routine work. Apart from that, there is also a final project called an innovation project.